STRATEGI PENINGKATAN KINERJA PEGAWAI DENGAN PERATURAN GUBERNUR DKI JAKARTA NOMOR 409 TAHUN 2016 TENTANG TUNJANGAN KINERJA DAERAH - Pulungan, Afriana; Iskandar, Abubakar; Rusliandy (Administratie: Jurnal Administrasi Publik, 2020)
This research is motivated by the State Civil Apparatus who have the same income between diligent employees and those who are not diligent in performing, thus making employees not enthusiastic in carrying out government tasks, therefore, the Governor of DKI Jakarta made Governor Regulation Number 409 of 2016 concerning regional performance allowances as a strategy to improve employee performance. Therefore, research is conducted on the effectiveness of this strategy in improving employee performance, it is important to conduct research, to prove the correlation between the implementation of the governor's Regulation No. 409 of 2016 policy with employee performance. This study used an associative approach with a population of 260 employees, which were then sampled using a technique from the Krejcie table as many as 155 employees. This sample data was taken using observation techniques, questionnaires, in-depth interviews, and literature studies. then the data taken in the field were analyzed by associative data analysis techniques. The results of the study indicate that there is a significant effect between the implementation of Governor Regulation number 409 of 2016 and employee performance. It is evident from the results of data analysis calculated using SPSS with a value of tcount > ttable (11.549 > 1.960).   Key words: Performance, Regulations, Benefits, Government Employees